Fatty acid composition, cardiovascular functionality, thermogravimetric-differential, calorimetric and spectroscopic behavior of pequi oil (Caryocar villosum (alb.) pers.) - Lorenzo, Natascha Dantas; Dos Santos, Orquídea Vasconcelos; Lannes, Suzana Caetano da Silva (FapUNIFESP (SciELO), 2021)
The objective of this investigation was to determine the composition and fatty acids profile of pequi (Caryocar villosum (Alb.) Pers.) oil, as well as its functionality in cardiovascular health, thermogravimetric-differential, calorimetric and spectroscopic behavior. The methodology used followed the standards established by the American Oil Chemists Society (AOCS). The results show oil with high nutritional value with predominance of unsaturated fatty acids (70%), especially oleic acid (52.67%) and linoleic acid (15.20%). The oil functionality indexes were expressed as cardiovascular protectors with low atherogenic and thrombogenic indexes (0.38 and 0.75) with a high hypocholesterolemic ratio (2.58). The oil pattern in the spectral bands 2980 to 2870cm-1 confirmed the predominance of unsaturated fatty acids with prominent peaks corresponding to double bonded chemical groups bands. The oil behavior under progressive temperature rises in an air atmosphere, supports the potential applications of this fruit by-product, that exhibits high thermal and oxidative stability with reduced mass loss at temperatures (267 °C and 376 °C) above those habitually used in food and industrial uses. These data show that unconventional fruits can increase and diversify the number of ingredients that can be used in food preparations and in the food, pharmaceutical, dermocosmetic, biofuel and other industries.
Keywords: Industry; Oil; Potential